2016
DOI: 10.1111/ajsp.12137
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the diverse cultural bases of social identity: Ingroup ties predict self‐stereotyping among individualists but not among collectivists

Abstract: On what basis do people form their social identities? To investigate this issue, the present research investigates crosscultural differences in self-stereotyping, a key outcome of social identification. In particular, the research tests the hypothesis that ingroup ties are a stronger predictor of self-stereotyping among people from individualist cultures than among people from collectivist cultures. In Study 1, university students (N = 117) completed measures of ingroup ties and self-stereotyping with respect … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Therefore, it indicated that individualism emphasizes their perceived control more than collectivism, while collectivism emphasizes the subjective norm more than individualism which is consistent with Bandyopadhyay and Fraccastoro (2007). Rubin et al (2016) also supported those individualists are driven by self-oriented factors. As for the outside force such as subjective norm, Chinese preservice teachers are higher than the American preservice teachers which is supported by Cohen et al (2016) who found that collectivism emphasizes context than individualism.…”
Section: Effects Of Online Teaching Attitude Subjective Norm and Perc...supporting
confidence: 54%
“…Therefore, it indicated that individualism emphasizes their perceived control more than collectivism, while collectivism emphasizes the subjective norm more than individualism which is consistent with Bandyopadhyay and Fraccastoro (2007). Rubin et al (2016) also supported those individualists are driven by self-oriented factors. As for the outside force such as subjective norm, Chinese preservice teachers are higher than the American preservice teachers which is supported by Cohen et al (2016) who found that collectivism emphasizes context than individualism.…”
Section: Effects Of Online Teaching Attitude Subjective Norm and Perc...supporting
confidence: 54%
“…Finally, generalizability of the results may be limited to individualist cultures and the role of culture should be addressed more directly in future studies. Among individualists, but not among collectivists, perceiving oneself as similar to ingroup members is positively related to supportive relationships with ingroup members (Rubin, Milanov, & Paolini, 2016). Moreover, among individualists relative to collectivists, the way people feel about themselves internally is more predictive of wellbeing and the perception that others view them positively (Hermann, Lucas, & Friedrich, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Group identification. Identification with the class was measured by using the 8 items from the identification scale developed by Cameron (2004) (8 items, e.g., "I often think about the fact I am a member of this class"; "I have a lot in common with the other classmates"), and 4 items adapted by Rubin, Milanov, and Paolini (2016)'s scale of self-stereotyping, assessing the degree to which participants perceived themselves as being similar to their classmates (e.g., "I think I am quite similar to the other students of the class"). Participants responded using a 5-point scale anchored to completely disagree (1) and completely agree (5); alpha = .86.…”
Section: Methodsmentioning
confidence: 99%